Scientific school of professor A. A. Petrovsky - M. I. Vashkevich; E. S. Azarov; U. A. Vishniakou (Informatika)
Two periods of scientific activity of Professor Alexander Alexandrovich Petrovsky, who was a member of the editorial board of the journal "Informatics" for 15 years (2004–2019), are presented. The main scientific results, his contribution to the development of the theory and to the hardware and software of the problem-oriented real-time systems and the processing of audio, speech and graphic information are shown, a list of the most significant works of the scientist is given.